Voltage Source Converter–Based Voltage Stiffness Compensator to Improve Grid Voltage Dynamics - Shang, Lei; Han, Chunyi; Dong, Xuzhu; Tian, Ye; Liu, Jianing (Frontiers in Energy Research, 2022)
This study proposes a novel voltage source converter (VSC)-based voltage dynamic regulatory device based on energy storage and virtual synchronous control, called as a rotating inertia and voltage stiffness compensator (RIVSC), to enhance grid voltage dynamics. In the proposed RIVSC, there is no inner cascaded current control, and the output voltage of the VSC, i.e., inner potential, is directly connected to the grid via a filter. Stiffness characteristic is featured in the inner potential of the RIVSC by the virtual synchronous control. On the basis of the stiffness characteristic, the RIVSC can naturally provide dynamic support for grid voltage. Compared to the traditional synchronous condenser, the proposed RIVSC is more flexible and contributes less short-circuit current. Compared to the existing power electronic-interfaced voltage regulatory device, dynamic support is natural without any time delay, and the proposed RIVSC can improve the dynamic performance of the grid voltage, which is helpful to alleviate the temporary overvoltage at the sending terminal. The basic principle, control methods, and application analysis are presented. Meanwhile, a 10 kW prototype is set up, and the experiment results validate the feasibility and effectiveness of the proposed RIVSC on improving grid voltage dynamics.